Anti-Inflammatory Effect of an Apigenin-Maillard Reaction Product in Macrophages and Macrophage-Endothelial Cocultures. (16th May 2019) - Zhou, Qian; Xu, Hui; Yu, Wenzhe; Li, Edmund; Wang, Mingfu
Abstract : Chronic inflammation is involved in the progression of various diseases, while dietary flavonoids are reported to possess antioxidative and anti-inflammatory properties against age-related diseases. Previously, an apigenin-Maillard reaction product, dimethylglyoxal apigenin (DMA), was identified by us and demonstrated to be antioxidative. In this study, we investigated the inhibitory effect of DMA on advanced glycation end product- (AGE-) induced inflammation in macrophages and macrophage-endothelial cocultures. Results showed that DMA remarkably inhibited the mRNA and protein expression of receptor for AGEs (RAGE), thereby inhibiting the production of ROS and proinflammatory cytokines, including tumor necrosis factor- (TNF-) α, interleukin (IL) 1, IL 6, and monocyte chemoattractant protein- (MCP-) 1 in RAW 264.7 cells. In the coculture system which was performed in the Boyden chamber, macrophage infiltration and adhesion to endothelial cells were significantly suppressed by DMA. Further study indicated that DMA decreased AGE-evoked IL 6 and MCP-1 secretion, which might be achieved through RAGE and its downstream-regulated transforming growth factor- (TGF-) β 1 and intercellular adhesion molecule (ICAM) 1 expression in the coculture system. In conclusion, our study demonstrates that DMA, a thermally induced compound, has anti-inflammatory activity in both macrophages and macrophage-endothelial cocultures, offering a promising approach for slowing down the development of chronic diseases.